2022
DOI: 10.1155/2022/7113793
|View full text |Cite
|
Sign up to set email alerts
|

α-Ketoglutarate Improves Meiotic Maturation of Porcine Oocytes and Promotes the Development of PA Embryos, Potentially by Reducing Oxidative Stress through the Nrf2 Pathway

Abstract: α-Ketoglutarate (α-KG) is a metabolite in the tricarboxylic acid cycle. It has a strong antioxidant function and can effectively prevent oxidative damage. Previous studies have shown that α-KG exists in porcine follicles, and its content gradually increases as the follicles grow and mature. However, the potential mechanism of supplementation of α-KG on porcine oocytes during in vitro maturation (IVM) has not yet been reported. The purpose of this study was to explore the effect of α-KG on the early embryonic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Oxidative stress also disrupts the mitochondrial membrane potential, which reduces the oxidative phosphorylation reaction and ATP synthesis ( Aiken, Cindrova-Davies & Johnson, 2008 ). Numerous studies have reported that antioxidant supplementation during IVM is commonly able to overcome mitochondria injury by reducing ROS levels ( Chen et al, 2022 ; Li et al, 2022 ; Liu et al, 2023 ). A previous study reported that Lut increased PGC-1α and nitric oxide levels, which would correct cellular impairment and may reduce mitochondrial ROS production, suggesting that Lut may promote mitochondrial biogenesis ( Suh, Chon & Choi, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress also disrupts the mitochondrial membrane potential, which reduces the oxidative phosphorylation reaction and ATP synthesis ( Aiken, Cindrova-Davies & Johnson, 2008 ). Numerous studies have reported that antioxidant supplementation during IVM is commonly able to overcome mitochondria injury by reducing ROS levels ( Chen et al, 2022 ; Li et al, 2022 ; Liu et al, 2023 ). A previous study reported that Lut increased PGC-1α and nitric oxide levels, which would correct cellular impairment and may reduce mitochondrial ROS production, suggesting that Lut may promote mitochondrial biogenesis ( Suh, Chon & Choi, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary negative regulator of NRF2 is KEAP1, which facilitates the degradation of NRF2 36 , 42 , 43 . Various molecules have been shown to stimulate NRF2 in reproductive tissues and cells, thereby reducing oxidative stress, such as quercetin 37 , N-acetylcysteine 44 , α-ketoglutarate 45 , sulforaphane 43 , 46 and melatonin 28 30 .…”
Section: Introductionmentioning
confidence: 99%
“…antioxidants [8,9] and cumulus features [10] can enhance the quality of porcine oocytes in IVM. Specifically, supplementation of antioxidant to IVM medium improved embryo quality, reduced early apoptosis levels, increased GSH content and reduced ROS accumulation, promoting embryonic development [11]. However, further research is needed to improve IVM of porcine oocytes.…”
Section: Introductionmentioning
confidence: 99%